Studi Perilaku Transportasi Angkutan Barang Antarkota Dengan Metode Analytical Hierarchy Proces - Marta, Andi; Yunus, Ahmad Yauri; Syahrir, Suryani (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
This research was conducted to find out the comparison of alternative modes of transportation for the most optimal transportation of goods from Bulukumba Regency to Makassar City using the AHP method. This study is quantitative and uses a survey approach. The results of this study indicate that Based on travel time, pickup is the fastest mode of freight transportation when compared to 2 axle trucks and 3- to 4-axle trucks. According to the volume of transport, the 345-axle truck is the best alternative mode of freight transportation and has a higher load capacity than 2 axle trucks and pick-ups. Meanwhile, pick-up is the most cost-effective mode of freight transportation when compared to 2 axle and 345 axle trucks. So, when looking at the criteria in terms of operational costs, travel time, range, and volume of transport, the 3-4-5 As truck is the most optimal alternative in choosing the capital for goods transportation on the Bulukumba Makassar route, followed by 2 As trucks, and finally, pick up.